Workplace spirituality in the public sector: a study of US water and wastewater agencies. Issue 3 (8th July 2019) - Farmer, Michele; Allen, Stuart; Duncan, Kathy; Alagaraja, Meera
Abstract : Purpose: This paper aims to understand water and wastewater industry leaders' perceptions of the current and future role of workplace spirituality, including the challenges and benefits of incorporating workplace spirituality in government utilities. Design/methodology/approach: The Delphi technique was used to gather input and gain consensus from an expert panel of executive level managers. Findings: The panel achieved consensus that workplace spirituality is evident in a higher sense of purpose for those working in the water and wastewater industry which is likely to be the greatest future benefit of workplace spirituality in the industry. Other central themes included making a positive environmental impact, going beyond compliance, collaborating with the community, creating a connection to peers and encouraging organizational belonging. Consensus was also achieved regarding obstacles to workplace spirituality's future role in the industry, including concerns about terminology and the need for supportive leadership. Practical implications: The water and wastewater industry face challenges including climate change, rising costs, aging infrastructure, increased regulatory requirements and a rapidly changing workforce. Workplace spirituality seems likely to support the industry in facing these challenges and can be promoted through encouraging a sense of purpose and meaning, collaborating with the community and recruiting individuals with resonant values and sense of calling. Originality/value: Workplace spirituality has received growing attention in the private sector. However, workplace spirituality research in the public sector is minimal. This expert panel of top leaders from US water and wastewater agencies provide insight into the role of workplace spirituality in the public sector.